Nuevos métodos y resultados del análisis espectral de cinco fricativas inglesas - Barreiro Bilbao, Silvia Carmen (Estudios Humanísticos. Filología, 1996)
This paper reports on a number of experiments carried out in order to describe the spectral characteristics of five English fricatives uttered in isolation and on a study of the influence on the spectrum of two variables, "subject" and "articulation". 7 male speakers with R.P. pronunciation were used as informants, producing 200 stimuli (40 per fricative). The material was analysed with a sonograph KAY 5500. As well as throwing new light on the spectral peak/formant frequencies and amplitudes there is a clear indication in evidence of the influence the aboye variables have on the spectrum of the fricatives. The results also show the intrinsic acoustic characteristics of each sound and their relationships with others. The data is presented in tables and illustrative graphs.